2021
DOI: 10.3389/fimmu.2021.754127
|View full text |Cite
|
Sign up to set email alerts
|

Divergent COVID-19 Disease Trajectories Predicted by a DAMP-Centered Immune Network Model

Abstract: COVID-19 presentations range from mild to moderate through severe disease but also manifest with persistent illness or viral recrudescence. We hypothesized that the spectrum of COVID-19 disease manifestations was a consequence of SARS-CoV-2-mediated delay in the pathogen-associated molecular pattern (PAMP) response, including dampened type I interferon signaling, thereby shifting the balance of the immune response to be dominated by damage-associated molecular pattern (DAMP) signaling. To test the hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 97 publications
(125 reference statements)
2
21
0
Order By: Relevance
“…Interestingly, a recent publication showed that the stimulation of human blood cells with SARS-CoV-2 proteins induced hallmarks of CR, including reduced proinflammatory cytokine production and T cell proliferation, and enhancement of phagocytosis and tissue remodeling 48 . Furthermore, there have been other studies which have shown through bioinformatic analysis and mathematical models that related biological responses dysregulated during severe Covid-19 infection overlap with that of all-cause sepsis 38 , 49 , 50 . The Mortality signature also captured 30-day mortality quite well, indicating that similar mechanisms arise during severe COVID-19 infection and all-cause sepsis when death is impending.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent publication showed that the stimulation of human blood cells with SARS-CoV-2 proteins induced hallmarks of CR, including reduced proinflammatory cytokine production and T cell proliferation, and enhancement of phagocytosis and tissue remodeling 48 . Furthermore, there have been other studies which have shown through bioinformatic analysis and mathematical models that related biological responses dysregulated during severe Covid-19 infection overlap with that of all-cause sepsis 38 , 49 , 50 . The Mortality signature also captured 30-day mortality quite well, indicating that similar mechanisms arise during severe COVID-19 infection and all-cause sepsis when death is impending.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis advances rapidly and the immune system is strongly involved, with 60% of the patients genome altered within 30 minutes of hospital admission 15 and cytokines and receptors linked to increased inflammation and innate immune response particularly affected 15 . IL6 and IL10 are pro- and antiinflammatory cytokines, that have been used as inflammation markers in several models 1619 and shown to increase production rates of altered neutrophils and monocytes in-vitro 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to apoptosis, which does not elicit inflammation, necrosis causes the release of damage-associated molecular patterns (DAMPs) such as high mobility group box (HMGB)-1 from dead cells [11][12][13] . Therefore, it is possible that the alveolar necrosis during early disease stages and subsequent release of DAMPs may drive disease progression in COVID-19-associated ARDS [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%